Penyadapan Dalam Tindak Pidana Korupsi Menurut Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi Dan Transaksi Elektronik - Ridwan Lubis, Muhammad (Universitas Islam Sumatera Utara, 2023)
The impact of progress in the field of information technology is that wiretapping is carried out to be used as evidence. One example of a criminal act that can be carried out by wiretapping is the crime of corruption which is an extraordinary crime. All wiretapping actions carried out by the Corruption Eradication Commission (hereinafter referred to as the Corruption Eradication Commission) and any agency that has wiretapping devices must be given strict limits and supervision. The research method used is normative juridical legal research with a normative juridical approach using secondary data in the form of primary legal materials, secondary legal materials and tertiary materials. Based on the research results, it is understood that the legal regulation of wiretapping in criminal acts of corruption according to the ITE Law is an act that is prohibited by the Law. ITE and its changes and the perpetrators can be subject to criminal sanctions. The exception to the provisions prohibiting wiretapping or interception is interception carried out in the context of law enforcement at the request of the police, prosecutor's office or other institutions whose authority is determined by law. One of the law enforcement institutions authorized by law to carry out wiretapping is the KPK. Keywords: Wiretapping, KPK, Corruption.